2022
DOI: 10.3390/gels8080501
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a New Cryogel Matrix for Covalent Immobilization of Catalase

Abstract: The advantages of cryogels for enzyme immobilization applications include their mechanical and chemical robustness, ease of production, superior porosity, and low cost. Currently, many researchers are exploring porous material-based systems for enzyme immobilization that are more efficient and economically viable. Here, poly(2-Hydroxyethyl methacrylate-co-allyl glycidyl ether) (p(HEMA-co-AGE)) cryogel matrices were synthesized via the free radical cryopolymerization method to be employed as the support materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The details of the covalent linking of α‐Glu enzyme onto Dex cryogels were given in the experimental section. The epoxy groups as commonly used functional groups for enzyme immobilization were utilized [35,36,43] . Before use, the prepared α‐Glu C @Dex cryogels were also washed with water, dried with a freeze dryer, and stored in closed tubes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the covalent linking of α‐Glu enzyme onto Dex cryogels were given in the experimental section. The epoxy groups as commonly used functional groups for enzyme immobilization were utilized [35,36,43] . Before use, the prepared α‐Glu C @Dex cryogels were also washed with water, dried with a freeze dryer, and stored in closed tubes.…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by the fact that upon the immobilization process, the active sites of the α‐Glu enzymes within the cryogel network are protected. As a result, the enzymes within cryogel are more stable at lower or higher temperatures in comparison to free enzymes allowing them to function somewhat more effectively in challenging reaction conditions [27,35,36] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking was a critical step in reducing non‐specific binding to avoid false positives 39 . Previous experiments revealed that unblocked AG cryogels have adsorption to proteins, which might lead to adsorption of non‐specific phages 40 . Comparing the phage output of once and double blocking during biopanning by AG cryogels, the experimental results showed that the number of non‐specific phages in double blocking was significantly lower at low wash solution volumes (<100 mL), suggesting that double blocking had a role in reducing the number of sites on cryogels induced to non‐specific adsorption (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…39 Previous experiments revealed that unblocked AG cryogels have adsorption to proteins, which might lead to adsorption of non-specific phages. 40 Comparing the phage output of once and double blocking during biopanning by AG cryogels, the experimental results showed that the number of non-specific phages in double blocking was significantly lower at low wash solution volumes (<100 mL), suggesting that double blocking had a role in reducing the number of sites on cryogels induced to non-specific adsorption (Figure 2A). However, it should be noted that the effect of double blocking on reducing non-specific phages was significantly reduced at high wash solution volumes, so a wash solution volume of 30 mL was finally selected in this experiment.…”
Section: Optimization Of Blocking Methodsmentioning
confidence: 99%